Adsorption of common greywater pollutants and nutrients by various biochars as potential amendments for nature-based systems: Laboratory tests and molecular dynamics - Sochacki, Adam; Lebrun, Manhattan; Minofar, Babak; Pohořelý, Michael; Vithanage, Meththika; Sarmah, Ajit K; Böserle Hudcová, Barbora; Buchtelík, Stanislav; Trakal, Lukáš (Environmental pollution (1987), 2024)
Spruce wood and Typha (wetland plant) derived biochars pyrolyzed at 350 °C and 600 °C were tested for their sorption affinity for organic pollutants (diclofenac, methylparaben, benzotriazole and sodium 1-decanesulfonate) and nutrients (nitrate, ammonium, phosphate and boron) commonly found in greywater. Batch and column studies combined with molecular dynamics modelling determined the sorption capacity, kinetics, and described the underlying mechanisms. The spruce biochar (600 °C) exhibited the highest sorption capacity mainly for the tested organics. The dynamic test performed for spruce biochar (600 °C) showed that the magnitude of desorption was low, and the desorbed amount ranged between 3 and 11 %. Molecular dynamics modelling (a computational tool for elucidating molecular-level interactions) indicated that the increased sorption of nitrate and boron on spruce biochar (600 °C) could be attributed to hydrophobic interactions. The molecular dynamics shows that predominant adsorption of organic pollutants was governed by π-π stacking, with a minor role of hydrogen-bonding on the biochar surface. In summary, higher pyrolysis temperature biochar yielded greater adsorption capacity greywater borne contaminants and the reaction temperature (10-34 °C) and presence of anionic surfactant had a limited effect on the adsorption of organic pollutants, suggesting efficacious application of biochar in general for greywater treatment in nature-based systems.
Keywords: Organic Chemicals; Adsorption; Boron; Molecular Dynamics Simulation; organické látky; Nutrients; Charcoal; dřevěné a živočišné uhlí; živiny; Nitrates; bor; simulace molekulární dynamiky; látky znečišťující životní prostředí; dusičnany; Environmental Pollutants; adsorpce